Corrosion Behavior of Mild Steel in Seawater from Northern Coast of Java and Southern Coast of Bali, Indonesia - S. Sundjono; Gadang Priyotomo; Lutviasari Nuraini; Siska Prifiharni (Journal of Engineering and Technological Sciences, 2017)
The corrosion behavior of mild steel in seawater was investigated using an immersion test and energy-dispersive X-ray spectroscopy in solutions from the sites of Muara Baru, Suramadu and Tol Mandara. As reference, solutions of 3.5% and 5% NaCl were prepared. Dissolved oxygen, salinity, conductivity, and total dissolved solids (TDS) were measured. It was found that uniform corrosion occurred on the mild steel during the immersion test. The corrosion resistance of the steel decreased with increasing exposure time. Since the magnitudes of conductivity, salinity and TDS of all test solutions were similar, it was concluded that dissolved oxygen (DO) and chloride ions play an essential role in inducing the corrosion risk of mild steel. Both parameters hinder the formation of a stable passive film on the surface of corroded mild steel.